Assessment of active tectonics in the Siwalik basin around the Subansiri river, NE India. Issue 1 (1st June 2022) - Singh, Archana; Gogoi, Bijoylakshmi; Bezbaruah, Devojit; Singh, Neelratan
Abstract: In this paper we evaluate the morphotectonics of the area around the Subansiri river in north-eastern India. Research focuses on understanding the impacts on areas experiencing active tectonic deformation. It also explains the variety of kinematics observed in the area from the Miocene to the present. The tectonics can explain some structures related to the extensional tectonics predominant in the region and the development of the minor and major morph structures driven by faults with different kinematics. We developed a morphotectonic evolutionary model for the area based on the morphotectonic analysis and geological mapping. Morphotectonic indices used to evaluate the tectonic activeness in this study are Mountain Front sinuosity Index, Valley Floor Width to Valley Height Ratio, Asymmetry Factor, Transverse Topographic Symmetry Factor, Mountain Front Steepness Index, Basin Shape Index and Stream Length Gradient Index. There are numerous lineaments present in the study area which are trending in NW-SE and NE-SW direction.